Multiplex genome editing for climate-resilient woody plants - Sen, Madhab Kumar; Mondal, Sunil Kanti; Bharati, Rohit; Severova, Lucie; Šrédl, Karel (Frontiers in Forests and Global Change, 2025)
Climate change is severely impacting global forest ecosystems, stressing woody plants due to rising temperatures, shifting precipitation patterns, and extreme weather events. These pressures threaten biodiversity and disrupt the essential roles forests play in carbon sequestration, timber production, and ecosystem stability. Traditional forest management strategies, such as selective breeding, cannot keep up with the rapid pace of climate change, given the long juvenile phase of trees. Multiplex genome editing, particularly through CRISPR technologies, offers a promising solution to accelerate the development of climate-resilient traits in woody plants. By simultaneously targeting multiple genes, multiplex CRISPR enables efficient modification of polygenic traits that govern stress tolerance, disease resistance, and other crucial resilience factors. This mini-review examines the potential of multiplex CRISPR technologies in forest management, breeding, and agroecological practices, showing how they can improve tree resilience and support sustainable forestry in response to the growing challenges of climate change.